THE EVOLUTION OF CONSUMER BEHAVIOR IN THE DIGITAL AGE: A SYSTEMATIC REVIEW OF E-COMMERCE MARKETING STRATEGIES - Akbar, Ilham; Rahimi, Faishal (Penelitian dan Pengembangan Ilmu, 2024)
Rapid changes in consumer behavior in the post-digital era demand adaptation of e-commerce marketing strategies, especially related to the increasing demand for value-based content. This research aims to identify and analyze effective marketing strategies in meeting consumer expectations for relevant, ethical and meaningful content. By using the approach Systematic Literature Review (SLR) through the PRISMA framework, this research finds that a value-based storytelling approach, the use of AI, and integration of sustainability are the main strategies in meeting this demand. The implications of this research indicate that e-commerce companies need to adopt value-based content to build stronger relationships with consumers and create long-term loyalty.